Modified percutaneous nephropexy for nephroptosis: Technical description and short-term results - Honglei Liu; Wenzhi Gao; Zheng Zhang; Kunlin Yang; Chang Meng; Bing Wang; Yangjun Han; Mingxin Diao; Chao Zuo; Minghua Zhang; Yingzhi Diao; Zhihua Li; et al. (Current Urology)
Abstract. Objectives. Percutaneous nephropexy (PCN) has been demonstrated as a feasible method for treating nephroptosis. This study describes an improved technique for PCN that better addresses the issue of nephroptosis. Materials and methods. We reviewed 4 patients who underwent the improved PCN procedure between January 2021 and January 2023. These patients were diagnosed with nephroptosis, with 1 case having both a narrow ureteropelvic junction and nephroptosis due to a kidney stone, and 3 cases having simple nephroptosis. Patient characteristics, perioperative data, and follow-up results were collected. Surgical success was determined by symptom relief (subjective success) and the absence of kidney descent by intravenous pyelography (objective success). Results. Preoperative computed tomography urography showed that all patients had hydronephrosis, with severe hydronephrosis in 75% (3/4) and moderate hydronephrosis in 25% (1/4) of cases. The mean operative time was 63.8 minutes (range, 45–95 minutes), and the mean blood loss was 5 mL (range, 5–50 mL). The mean length of hospital stay was 4.5 days (range, 3–6 days). The mean time to removal of the nephrostomy tube was 2 months (range, 1–4 months). No serious complications (Clavien-Dindo grade ≥3) occurred during or after the procedure. The mean postoperative serum creatinine level was 54.75 μmol/L (range, 43–65 μmol/L). The mean follow-up time was 6.25 months (range, 4–8 months). The objective and subjective success rates were both 100%. Conclusions. The improved PCN procedure that was used in this study is feasible and provides a good option for treating nephroptosis.